El precio de los cuerpos maltratados : discursos judiciales para comprar la memoria de las marcas de dolor. Chile, 1773-1813 - María Eugenia Albornoz Vásquez (Nuevo mundo - Mundos Nuevos, 2009)
Violence exerted over bodies leave physical and spiritual marks; scars, mutilations, fears. In the Chilean colonial society there were individuals that after being exposed to situations of power or moral abuse turned to the judicial system in order to obtain the compensations stipulated by law. Some opted for the pecuniary compensations that aimed at amending through monetary payments the consequences of lashes, burns, beatings and cuts. The analysis of judicial proceedings for slanders provides an opportunity to explore how the compensations based on monetary valuations of the damage operated from a discursive and practical point of view, unveiling, among other things, the ways in which physical infliction was assessed and the judicial strategies deployed to demand compensation. More important than previously stated, the analysis of judicial processes invites to think about the place and value of abused masculine and feminine bodies, and the social and cultural representations of individuals and communities.